A critical analysis of the South African turnover tax system - Chiromo, Samuel John (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
The objective of the turnover tax system is to reduce the administrative burden on micro businesses and to contribute positively to boosting these businesses and the economic growth of South Africa. The over-arching goal of this research was to analyse the South African turnover tax to investigate to what extent the turnover tax system complies with generally accepted principles of a good tax system. The research was conducted within an interpretative post-positivism paradigm, applied a qualitative research methodology, and a doctrinal research method. A detailed review of the literature was conducted to establish the nature of South African turnover tax system and the extent of its compliance with generally accepted principles of a good tax system. The literature review included an in-depth analysis of the South African turnover tax system, an in-depth analysis of generally accepted principles of a good tax system, and an investigation of the extent to which turnover tax system complies with various elements of the principles of a good tax system. It was found in this study that the turnover tax system does not comply with certain of the elements of generally accepted principles of a good tax system and the study proposed several recommendations for the improvement of the turnover tax system. These recommendations include the establishment of training initiatives for micro business owners, reviewing the regulations pertaining to turnover tax and providing digital administration of turnover tax.
Keywords: Small business -- Taxation -- South Africa; Small business -- South Africa -- Finance; Turnover tax -- South Africa; Government aid to small business -- South Africa; Tax incentives -- South Africa